A Regulable Internal Cavity inside a Resorcinarene‐Based Hemicarcerand. Issue 26 (1st April 2020) - Harada, Kentaro; Sekiya, Ryo; Haino, Takeharu
Abstract: Covalent organic capsules, such as carcerands and hemicarcerands, are an interesting class of molecular hosts. These container molecules have confined spaces capable of hosting small molecules, although the fact that the size of the inner cavities cannot be changed substantially limits the scope of their applications. The title covalently linked container was produced by metal‐directed dimerization of a resorcinarene‐based cavitand having four 2, 2′‐bipyridyl arms on the wide rim followed by olefin metathesis at the vertices of the resulting capsule with a second‐generation Grubbs catalyst. The covalently linked bipyridyl arms permit expansion of the inner cavity by demetalation. This structural change influences the molecular recognition properties; the metal‐coordinated capsule recognizes only 4, 4′‐diacetoxybiphenyl, whereas the metal‐free counterpart can encapsulate not only 4, 4′‐diacetoxybiphenyl, but also 2, 5‐disubstituted‐1, 4‐bis(4‐acetoxyphenylethynyl)benzene, which is 9.4 Å longer than the former guest. Molecular mechanics calculations predict that the capsule expands the internal cavity to encapsulate the long guest by unfolding the folded conformation of the alkyl chains, which demonstrates the flexible and regulable nature of the cavity. Guest competition experiments show that the preferred guest can be switched by metalation and demetalation. This external‐stimuli‐responsive guest exchange can be utilized for the development of functional supramolecular systems controlling the uptake, transport, and release of chemicals. Abstract : Flexible accommodation : A resorcinarene‐based capsule with a size‐regulable internal cavity was realized. The alkyl chains connecting its 2, 2′‐bipyridyl arms permit expansion and contraction of the cavity by demetalation and metalation. The reversible size change of the capsule enables switching of its molecular recognition properties.